Sensitivity Analysis in MADM Methods: Application of Material Selection - Yazdani, Morteza; Zavadskas, Edmundas Kazimieras; Ignatius, Joshua; Doval Abad, Manuel (Inžinerinė ekonomika, 2016)
Material evaluation studies are getting very strategic subject in design and engineering. Decision about effective modeling of material selection framework is always a concern for management of manufacturing and production.  This study is involved with a new approach to select materials based on expert’s policy and multi attribute decision making theory due to some technical conflicting variables and quantity of materials. Weighting method SWARA for the first time is applied in material selection and then to prioritize candidate material list WASPAS and MOORA are employed. To verify material ranking outcomes, sensitivity analysis as putting new normalization tool for WASPAS and MOORA is performed. Two real material selection case studies are presented to configure and model effective structure of material selection database. DOI: http://dx.doi.org/10.5755/j01.ee.27.4.14005